Chemical characterisation by UPLC‐Q‐ToF‐MS/MS and antibacterial potential of Coffea arabica L. leaves: A coffee by‐product. Issue 7 (1st July 2022) - Mesquita Júnior, Gilmar Alves de; da Costa, Ygor Ferreira Garcia; Mello, Valéria de; Costa, Fabiano Freire; Rodarte, Mirian Pereira; Costa, Juliana de Carvalho da; Alves, Maria Silvana; Vilela, Fernanda Maria Pinto
Abstract: Introduction: Coffea arabica L. leaves are considered a by‐product of the coffee industry however they are sources of several bioactive compounds. Objectives: This study aimed to evaluate the chemical composition and the in vitro antibacterial activity of the lyophilised ethanol extract of arabica coffee leaves (EE‐CaL). Material And Methods: The chemical characterisation of EE‐CaL was performed using ultra‐performance liquid chromatography coupled to quadrupole time‐of‐flight mass spectrometry (UPLC‐Q‐ToF‐MS/MS). The in vitro antibacterial effect of EE‐CaL was evaluated using the broth microdilution method and the adapted drop plate agar method to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC), respectively. Results: The chemical analysis of EE‐CaL revealed the presence of compounds from the alkaloid class, such as trigonelline and caffeine, in addition to the phenolic compounds such as quinic acid, 5‐caffeoylquinic acid, caffeic acid‐ O ‐hexoside, mangiferin, (epi)catechin, (epi)catechin monoglucoside and procyanidin trimer. Regarding the antibacterial potential, EE‐CaL was active against Gram‐positive and Gram‐negative bacteria, being more effective against Escherichia coli (ATCC 25922) (MIC = 2500 μg/mL and bactericidal effect). Conclusion: The results of this research suggest that coffee leaves, a by‐product, possess compounds with antibacterial properties. Thus, further studies with coffee leaf extracts must be carried out to relate the compounds present in the extract with the antibacterial activity and find the mechanisms of action of this extract against bacteria. Abstract : Coffea arabica L. leaves are considered a by‐product of the coffee industry however they are sources of several bioactive compounds. This study aimed to evaluate the chemical composition and the in vitro antibacterial activity of the lyophilised ethanol extract of arabica coffee leaves (EE‐CaL). The results of this research suggest that coffee leaves, a by‐product, contains compounds with antibacterial properties. Furthermore, this is the first time that caffeic acid‐ O ‐hexoside, (epi)catechin monoglucoside and procyanidin trimer have been detected in coffee leaves.